Growth and quality of conilon coffee seedlings produced at different containers and shading levels - Dandengo, Maria Christina J. D.; de Sousa, Elias Fernandes; dos Reis, Edvaldo Fialho; Gravina, Geraldo de Amaral (Coffee Science - ISSN 1984-3909, 2014)
The objective of this study was to evaluate the influence of two containers and different levels of shading in the growth and quality of conilon coffee seedlings, as well as to perform a path analysis to characterize the interrelationships between growth variables and quantify their direct and indirect effects on the quality of seedlings. The experimental design used was completely randomized, distributed in split-plot 2 x 4 schema, with ten repetitions. The type of containers tested were 120 ml polyethylene tubes and plastic bags with 770 cc, filled with standard substrate. The levels of shadow tested were 0% (full sun), 30%, 50% and 75%. The results showed that plants grew better in bags than in tubes, except the 30% level of shading. The shaded seedlings showed better quality and growth than the ones kept in full sun. Dickson index of quality was efficient to indicate the quality of the conilon coffee seedlings in separate containers and shading levels. The relationship between plant height / stem diameter and dry matter of the aerial part / roots translate information that assist the proper handling of seedlings in nurseries. The total dry matter and stem diameter are the more likely variables to indicate the quality of the conilon coffee seedlings, due to the higher degree of correlation with the Dickson index of quality.